Hind wing morphology facilitates discrimination between two sibling species: Leiopus nebulosus and L. linnei (Coleoptera: Cerambycidae) - Rossa, Robert; Goczał, Jakub; Tofilski, Adam (Zootaxa, 2017)
The study focused on two sibling beetle species: Leiopus nebulosus (Linnaeus, 1758) and L. linnei Wallin, Nylander & Kvamme, 2009. These species are very similar morphologically and their identification is difficult and possible only by experienced taxonomists. A supporting method for identification of L. nebulosus and L. linnei based on hind wings measurements was developed. The study was based on 115 specimens of L. linnei and 45 specimens of L. nebulosus. The correctness of identification of L. nebulosus amounted to 95.56%, and of L. linnei – 97.39%. The obtained model facilitates reliable identification of L. nebulosus and L. linnei also by less experienced entomologists. Geographical distributions of both species were summarized based on faunistic data from 39 scientific papers. The results show that both species have a Western-Palearctic distribution. Their distribution ranges are markedly overlapping. However, L. linnei is the species reported from larger number of localities, and observed more often.